Terrorism and the Fate of Dictators. (July 2015) - Aksoy, Deniz; Carter, David B.; Wright, Joseph
Abstract : The authors study the influence of domestic political dissent and violence on incumbent dictators and their regimes. They argue that elite with an interest in preserving the regime hold dictators accountable when there is a significant increase in terrorism. To pinpoint the accountability of dictators to elite who are strongly invested in the current regime, the authors make a novel theoretical distinction between reshuffling coups that change the leader but leave the regime intact and regime-change coups that completely change the set of elites atop the regime. Using a new data set that distinguishes between these two coup types, the authors provide robust evidence that terrorism is a consistent predictor of reshuffling coups, whereas forms of dissent that require broader public participation and support, such as protests and insurgencies, are associated with regime-change coup attempts. This article is the first to show that incumbent dictators are held accountable for terrorist campaigns that occur on their watch.